1998
DOI: 10.1007/s002130050539
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic activity and the discriminative stimulus effects of mu opioids in pigeons: importance of training dose and attenuation by the D 3 agonist (±)-7-OH-DPAT

Abstract: The present investigation examined the effects of several dopaminergic compounds in pigeons trained to discriminate either a 0.1 (low) or 5.6 (high) mg/kg dose of the mu opioid butorphanol from saline. Various dopamine (DA) re-uptake inhibitors, releasers, a D1 agonist, a D2 agonist and a D3 agonist engendered partial substitution (50-79% butorphanol responding) for the butorphanol stimulus in the low-dose group. In the high-dose group, with a few exceptions, these compounds produced predominately saline respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…With respect to DA substitution profiles, only cocaine, GBR 12909, and R-(Ϫ)-NPA engendered partial-to-full substitution for the training dose of cocaine, and none of the DA agonists engendered heroin-like DS effects regardless of dose. These findings differ from some studies (Cook and Picker, 1998;Lamas et al, 1998;Platt et al, 1999) in which cocaine and other stimulants substituted for heroin or morphine in rats, pigeons, and squirrel monkeys. It is interesting to note that in nondependent humans trained in a three-choice drug discrimination procedure with saline, hydromorphone, and pentazocine as the training stimuli, amphetamine did not generalize to hydromorphone but did partially generalize to both pentazocine and saline (Bickel et al, 1989).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…With respect to DA substitution profiles, only cocaine, GBR 12909, and R-(Ϫ)-NPA engendered partial-to-full substitution for the training dose of cocaine, and none of the DA agonists engendered heroin-like DS effects regardless of dose. These findings differ from some studies (Cook and Picker, 1998;Lamas et al, 1998;Platt et al, 1999) in which cocaine and other stimulants substituted for heroin or morphine in rats, pigeons, and squirrel monkeys. It is interesting to note that in nondependent humans trained in a three-choice drug discrimination procedure with saline, hydromorphone, and pentazocine as the training stimuli, amphetamine did not generalize to hydromorphone but did partially generalize to both pentazocine and saline (Bickel et al, 1989).…”
Section: Discussioncontrasting
confidence: 95%
“…These findings strongly implicate both D1-and D2-like receptor mechanisms in the ability of cocaine to attenuate the DS effects of heroin. Previous studies in rats have shown that D2-like agonists can attenuate the behavioral effects of heroin and other high efficacy opioid agonists (Cook and Picker, 1998;Cook and Beardsley, 2004). Both R-(Ϫ)-NPA and quinpirole, another D2-like agonist, have been shown to inhibit selfadministration of heroin under a progressive ratio schedule in rhesus monkeys (Rowlett et al, 2007).…”
Section: Asymmetric Cocaine-heroin Interactions In Monkeys 993mentioning
confidence: 99%
See 2 more Smart Citations
“…There remains a possibility, however, that interactions between the opioid and DA systems in heroin-trained subjects may be unique to a specific DA receptor subtype. For example, Cook and Picker (1998) demonstrated an attenuation of the DS effects of a agonist by the D 3 subtype-preferring agonist 7-OH-DPAT (7-hydroxy-2-dipropylaminotetralin).…”
Section: Discussionmentioning
confidence: 99%